2020
DOI: 10.1111/1749-4877.12486
|View full text |Cite
|
Sign up to set email alerts
|

The differential genetic signatures related to climatic landscapes for jaguars and pumas on a continental scale

Abstract: Modern and paleoclimate changes may have altered species dynamics by shifting species’ niche suitability over space and time. We analyze whether the current genetic structure and isolation of the two large American felids, jaguar (Panthera onca) and puma (Puma concolor), are mediated by changes in climatic suitability and connection routes over modern and paleoclimatic landscapes. We estimate species distribution under 5 climatic landscapes (modern, Holocene, last maximum glaciations [LMG], average suitability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 102 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…We used within‐population GD data collected and as presented elsewhere (Azizan & Paradis, 2021), including 10 additional studies published since 2020 found in Web of Science and Google Scholar ( n = 175). These additional studies provided data for Geoffroy's cat ( Leopardus geoffroyi ) (Bou et al, 2021), puma (Gallo et al, 2020; Zanin et al, 2021), European lynx (Herrero et al, 2021), jaguars (Kantek et al, 2021; Zanin et al, 2021), snow leopard (Korablev et al, 2021; Singh, Singh, Joshi, Chandra, et al, 2022), bobcat (Cancellare et al, 2021; Miller‐Butterworth et al, 2021) and leopard (Singh, Singh, Joshi, Singh, et al, 2022). Detailed methods for assembling this data set can be found elsewhere (Azizan & Paradis, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…We used within‐population GD data collected and as presented elsewhere (Azizan & Paradis, 2021), including 10 additional studies published since 2020 found in Web of Science and Google Scholar ( n = 175). These additional studies provided data for Geoffroy's cat ( Leopardus geoffroyi ) (Bou et al, 2021), puma (Gallo et al, 2020; Zanin et al, 2021), European lynx (Herrero et al, 2021), jaguars (Kantek et al, 2021; Zanin et al, 2021), snow leopard (Korablev et al, 2021; Singh, Singh, Joshi, Chandra, et al, 2022), bobcat (Cancellare et al, 2021; Miller‐Butterworth et al, 2021) and leopard (Singh, Singh, Joshi, Singh, et al, 2022). Detailed methods for assembling this data set can be found elsewhere (Azizan & Paradis, 2021).…”
Section: Methodsmentioning
confidence: 99%